Institutional Features of Cluster Development in the Russian Federation - Maksimova, Tatiana P.; Milyaev, Konstantin V. (International Review of Management and Marketing, 2016)
The paper has presented the author’s views on the subject of conceptual approaches to research the features of reformations in the agrarian sphere of economy. It has paid attention to the fact that an objective compelling reason for an essential reformation of the agrarian sphere of national economy is to promote national food security. The authors think that one of the best ways to change business forms and patterns is to generate agro-industrial clusters in Russia. The authors of the paper believe that agro-industrial clusters have the potential to become in the current context an adequate response in choosing future paths to reform the agrarian sphere of the Russian Federation economy considering the common inner instability within the country as well as the constantly changing foreign-economic challenges, including food sanctions. The authors consider some theoretical aspects of creating agro-industrial clusters in the system of national economy, pay their attention to historical aspects of dialectic development of the cluster theory, analyze a possibility of exploiting advantages of clusters in relation to the agrarian sphere of national economy, carry out a development of the author’s hypothesis of an official functionally structured modeling of organization of agro-industrial clusters and offer to consider agro-industrial clusters as a possible way of the reformation of business patterns in economy of the Russian Federation. Special attention is paid to agro-business holding companies as to key elements of creating subject agro-industrial clusters. The paper emphasizes relevance of the arrangement of necessary institutional conditions to create effective agro-industrial clusters in Russia. Keywords: agro-industrial clusters, investment attractiveness, quality of life JEL Classifications: E22, C38, Q13